2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6224584
|View full text |Cite
|
Sign up to set email alerts
|

A new tentacles-based technique for avoiding obstacles during visual navigation

Abstract: Abstract-In this paper, we design and validate a new tentacle-based approach, for avoiding obstacles during appearance-based navigation with a wheeled mobile robot. In the past, we have developed a framework for safe visual navigation. The robot follows a path represented as a set of key images, and during obstacle circumnavigation, the on-board camera is actuated to maintain scene visibility. In those works, the model used for obstacle avoidance was obtained using a potential vector field. Here, a more sophis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Indeed, if such deviation is not encountered during training, the robot will have no memory of what it sees after deviating. Recent improvements by Cherubini, Spindler, and Chaumette () have shown promising results in overcoming this difficulty.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, if such deviation is not encountered during training, the robot will have no memory of what it sees after deviating. Recent improvements by Cherubini, Spindler, and Chaumette () have shown promising results in overcoming this difficulty.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast with those works, our approach does not require the robot pose, and exploits the robot geometric and kinematic characteristics (this aspect will be detailed later in the paper). A detailed comparison between the potential field and the tentacle techniques is given in [Cherubini et al 2012]. In that work, we showed that with tentacles, smoother control inputs are generated, higher velocities can be applied, and only dangerous obstacles are taken into account.…”
Section: Introductionmentioning
confidence: 98%
“…The success of the technique depends on being able to quickly and robustly match the input visual features despite changes in lighting conditions or in the presence of dynamic obstacles. Another concern is how to get back to the set route when the robot has to deviate from it momentarily while avoiding novel obstacles (pedestrians), although recent improvements [7] have shown promising results.…”
Section: Introductionmentioning
confidence: 99%